2023
DOI: 10.1021/acsaenm.3c00013
|View full text |Cite
|
Sign up to set email alerts
|

MXene as a Superior Charge-Transport Layer in an MXene–BiFeO3–ZnO Nanocomposite for Photocatalytic Disintegration of Antacids

Abstract: In recent times, the environmental and pure water crisis requires many types of scientific evaluation to handle the issues caused by different pharmaceutical drugs. The current work involves the synthesis of ternary hybrid nanomaterials based on Ti3C2MXene–BiFeO3 (BFO)–ZnO and their applications as photocatalysts for the disintegration of antacids. The introduction of the two-dimensional (2D) MXene layer in the BFO–ZnO heterostructures not only creates additional reaction hotspots but also enhances charge-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 82 publications
(126 reference statements)
0
10
0
Order By: Relevance
“…The MXBZ nanocomposite was fabricated using a low-cost hydrothermal process. 36 A homogeneous solution of BZ was prepared by mixing 100 mg of BZ powder and 30 mL of water using an ultrasonication bath at 60 °C. To fabricate the MXBZ heterostructure with a variation of MXene weight percentage in the MXBZ nanocomposite, 2 mg, 5 mg, 8 mg, and 15 mg of the MXene nanosheet was added to that solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MXBZ nanocomposite was fabricated using a low-cost hydrothermal process. 36 A homogeneous solution of BZ was prepared by mixing 100 mg of BZ powder and 30 mL of water using an ultrasonication bath at 60 °C. To fabricate the MXBZ heterostructure with a variation of MXene weight percentage in the MXBZ nanocomposite, 2 mg, 5 mg, 8 mg, and 15 mg of the MXene nanosheet was added to that solution.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the previously documented references also yield similar results. 36,48 The fact that the XRD peaks of MXene are significantly lower in intensity than the highly crystalline BFO or ZnO also explains the absence of prominent peaks associated with MXene in the MXBZ nanocomposite. This disparity in intensity makes it difficult to indicate distinct peaks attributed to MXene within the composite material.…”
Section: B Structural Characterization Of Mxbzmentioning
confidence: 99%
See 1 more Smart Citation
“…), Ti 3 C 2 T x MXene is the most popular 2D material because of its easy delamination into a monolayer by HF treatment, which can help to explore the real 2D characteristics of MXene. Pristine Ti 3 C 2 MXene is expected to form a Schottky junction with semiconductors, which is usually formed at the semiconductor–metal interface by utilizing the difference in the work function of metal and semiconductor. Several studies showed that conductive Ti 3 C 2 MXene can effectively promote the photocatalytic performance of TiO 2 , ZnO, CeO 2 , g-C 3 N 4 , CdS, Bi 2 S 3 , and ternary semiconductors by superior interface engineering. The enhanced catalytic activity of TiO 2 is mainly due to the efficient separation of charge carriers at the heterojunctions formed between Ti 3 C 2 T x and TiO 2 . , Unlike conventional metallic materials, 2D Ti 3 C 2 MXene used as a gas-sensing metal reveals excellent performance by modulation of in situ-built Ti 3 C 2 –TiO 2 Schottky barriers within the sensing channel. Likewise, the rutile TiO 2 nanoparticles obtained from Ti 3 C 2 MXene oxidations are proven to be beneficial for the electron transporting layer in perovskite solar cells owing to their excellent defect and trap-assisted recombination suppression properties at the interface. , …”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Furthermore, the edge architecture and extensive surface functional groups within MXene quantum dots facilitate the formation of heterojunctions to semiconductor materials, establishing strong built-in electric fields as well as tight interfacial contacts. 27,28 The synergistic effect can significantly hasten the transfer and separation of photo-generated electrons and holes in heterojunction contact interfaces, which is the key factor in improving photocatalytic performance. Recently, several studies have shown that the construction of heterojunctions of MXene quantum dots with Cu 2 O, g-C 3 N 4 , and SiC significantly improved photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%